Optimasi Kinerja Steam Turbine Generator 4 Pada Power Plant 2 Utilities dengan Menaikkan Inlet Steam Flow (Studi Kasus PT. X) - I Ketut Warsa; Sahrul Rhomadan; Megawati, Eka (Jurnal Ilmiah Teknik Kimia, 2025)
Electrical energy has an important role for home needs such as washing machines and irons, as well as for the industrial sector such as power plants and other infrastructure. To create electrical energy, a system is needed which is known as a power plant.. At PT. X electrical energy is produced from the Power Plant which contains supporting equipment, one of which is the Steam Turbine Generator. A Steam Turbine generator is a machine that produces electrical energy from the use of hot steam converted into mechanical energy which is connected by the turbine shaft to the generator. In the refinery operation process, it is very important to know the optimal performance of the Steam Turbine Generator. The research aims to obtain the optimization value of Steam Flow Steam Turbine Generator 4 at Power Plant 2 and to analyze the resulting performance optimization comparison. Optimizing the performance of Steam Turbine Generator 4 Power Plant 2 was carried out by increasing the Steam Flow by 5 Ton/day from 23.80 Ton/day to 63.80 Ton/day. Optimal performance on Steam Turbine Generator 4 Power Plant 2 is obtained at a Steam Flow of 63.80 Tons/day with an electrical power of 12.6 MW which will produce an efficiency value of 80.76%.